1989
DOI: 10.1016/s0741-5214(89)70014-8
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of acute renal artery occlusion after percutaneous transluminal angioplasty

Abstract: Four patients with •occlusive complications after percutaneous~luminal renal artery angioplasty (PTA) have been treated from July 1, 1984, to March 14, 1988. During this interval such renal artery angioplasties were performed in 44 patients. Two resulted in complete main renal artery occlusion, one angioplasty resulted in occlusion of a stenotic nal artery bypass graft, and one renal PTA resulted in segmental .branch renal artery narrowing, which was thought to represent a dissection. The latter segmental-rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In the last two decades, an increasing number of reports have appeared on the use of selective lytic therapy in the management of these cases. [2][3][4][5][6]8,[10][11][12] In the study of Salam et al, 8 70% of the patients had their renal perfusion restored by lytic therapy, but only 30% recovered normal function of the affected kidney, a result still comparable to surgical revascularization for acute RA occlusion. In fact, in the study published by Ouriel et al 2 of the 13 patients treated surgically, successful restoration of renal function was obtained in only 38%.…”
Section: Discussionmentioning
confidence: 99%
“…In the last two decades, an increasing number of reports have appeared on the use of selective lytic therapy in the management of these cases. [2][3][4][5][6]8,[10][11][12] In the study of Salam et al, 8 70% of the patients had their renal perfusion restored by lytic therapy, but only 30% recovered normal function of the affected kidney, a result still comparable to surgical revascularization for acute RA occlusion. In fact, in the study published by Ouriel et al 2 of the 13 patients treated surgically, successful restoration of renal function was obtained in only 38%.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases emergency reconstruction has proved to be an effective and reliable mode of therapy. 22,23 The exact place of extracorporeal reconstruction remains an important issue. It has well been demonstrated that complex renovascular lesions can be successfully treated by in situ techniques including operative dilation.…”
Section: Discussionmentioning
confidence: 99%